2022
DOI: 10.1186/s13018-022-03207-0
|View full text |Cite
|
Sign up to set email alerts
|

Circ-FOXM1 promotes the proliferation, migration and EMT process of osteosarcoma cells through FOXM1-mediated Wnt pathway activation

Abstract: Background Osteosarcoma (OS) is a malignant bone tumor that commonly occurs in adolescents with a high mortality rate and frequent pulmonary metastasis. Emerging evidence has suggested that circular RNAs (circRNAs) are important regulators in multiple biological activities of carcinomas. Nevertheless, the role of circRNAs derived from forkhead box M1 (FOXM1), a well-accepted modulator of OS progression, has not been discussed in OS. Methods Quantit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…Likewise, Chen et al [ 64 ] found that Wnt-induced deubiquitination of FoxM1 is a novel and important mechanism controlling canonical Wnt signaling and cell proliferation. Furthermore, FoxM1-mediated activation of the Wnt pathway can promote cell proliferation, migration, and epithelial-mesenchymal transition [ 65 ]. Here, we discovered that β -catenin expression lowered following LPS therapy but was reversed by BMSCs-Vector or BMSCs-FoxM1, and the reversal was more pronounced with BMSCs-FoxM1.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, Chen et al [ 64 ] found that Wnt-induced deubiquitination of FoxM1 is a novel and important mechanism controlling canonical Wnt signaling and cell proliferation. Furthermore, FoxM1-mediated activation of the Wnt pathway can promote cell proliferation, migration, and epithelial-mesenchymal transition [ 65 ]. Here, we discovered that β -catenin expression lowered following LPS therapy but was reversed by BMSCs-Vector or BMSCs-FoxM1, and the reversal was more pronounced with BMSCs-FoxM1.…”
Section: Discussionmentioning
confidence: 99%
“…miRNAs: It has been shown that miR-320a and miR-320b function as OS inhibitors [91,92]. Overexpression of these miRs promotes downregulation of FOXM1 expression in OS cells [93]. Low expression of miR-361-5p was observed in OS tissues and cell lines.…”
Section: • Foxm1 Foxm1 (Foxhead Box M1mentioning
confidence: 99%